Impact of Ultra High-risk Genetics on Real-world Outcomes of Transplant-eligible Multiple Myeloma Patients. Issue 2 (25th February 2023) - Panopoulou, Aikaterini; Easdale, Sandra; Ethell, Mark; Nicholson, Emma; Potter, Mike; Giotas, Asterios; Woods, Helena; Thornton, Tracy; Pawlyn, Charlotte; Boyd, Kevin D.; Kaiser, Martin F.
Abstract : Refined prediction of early relapse following standard-of-care (SoC) autologous stem cell transplant (ASCT) in newly diagnosed multiple myeloma (NDMM) could inform real-world risk-stratified post-ASCT strategies. We investigated the impact of double hit genetics (≥2 adverse markers: t(4;14), t(14;16), t(14;20), gain(1q), del(17p)) on outcome in 139 NDMM patients who underwent SoC ASCT between January 2014 and October 2019 at our center. Double hit genetics were associated with a significantly shortened progression-free survival (hazard ratio [HR] = 4.27, P < 0.001) and overall survival (HR = 4.01, P = 0.03), and characterized most early relapses. Our results support the real-world utility of extended genetic profiling for improved risk prediction in NDMM.